Structural strength analysis of a tourist minicar knuckle using finite element analysis - Hanafi, Agung Fauzi; Umar, Mega Lazuardi; Prasetya Dharma Yudha, I Gusti Ngurah Agung Satria; Siregar, Ansor Salim (Politeknik Negeri Lhokseumawe, 2026)
The design of components for vehicles used in tourist areas must be efficient, safe, and economical. The steering knuckle is a vital component in the vehicle's suspension and steering systems, playing a crucial role in transferring loads, connecting the wheel to the steering mechanism, and supporting braking components. This research aims to design, analyze, and fabricate a steering knuckle for a mini tourist car with a total mass of 300 kg using plain carbon steel. The design and strength analysis were evaluated using the open-source Finite Element Analysis (FEA) software PrePoMax to investigate stress distribution, deformation, and the factor of safety. The FEA results showed a maximum Von Mises stress of 86.27 MPa, well below the material's yield strength, a maximum deformation of 0.126 mm, and a minimum safety factor of 2.72, confirming a robust design. The component was designed to accommodate a 30204 tapered roller bearing. The fabrication process, encompassing cutting, machining, and welding, successfully produced a functional prototype validated through direct installation and load testing on the vehicle. This study confirms that plain carbon steel is a reliable and economical material for structural components in lightweight vehicle applications and provides a pragmatic engineering framework for developing cost-effective automotive components.